The Effect Of Price, Product Variation, And Promotion On Purchase Decisions At Niky Cokelat Kediri - Danaraja, Riestu; Damayanti, Susi; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim :This study examines the influence of price, product variation, and promotion on purchases of UMKM Niky Cokelat Kediri. Design/Method/Approach :This study uses causal quantitative descriptive research. Sampling was done purposively. This study involved 40 customers of UMKM Niky Cokelat Kediri. This study uses SPSS 25 to measure it. Research Findings :The t-test shows that price, product variety, and promotion partially affect purchasing decisions. The F-test shows that price, product variety, and promotion simultaneously affect purchasing decisions. Theoretical contribution/Originality :UMKM Niky Cokelat Kediri must use methods such as competitive prices, a variety of goods according to needs, and attractive promotions such as discounts or loyalty programs so that its appeal is greater. Practitionel/Policy implications :UMKM Niky Cokelat Kediri, is advised to continue to improve purchasing decisions on several factors such as price, by providing discounts and special offers. Product variation factors, by creating product variants and designs according to needs. And for the promotion factor by promoting through social media, such as using digital platforms. Research limitations:This study shows that additional characteristics influence purchasing decisions, which can be used to improve future studies.